The problems and development strategy of China’s outward FDI based on the comparison between China and Japan - LIU, BEI (2011)
This study investigates the current general situation of China’s outward FDI, its characteristics and geographical and sectors distribution. On the basis of current situation of outward FDI in China, the main determinants of outward FDI both in China and Japan has been evaluated. The focus is the main determinants in the home countries, the extent to which those main determinants affect the volume and growth of outward FDI in China and in Japan separately. In addition, the differences of outward FDI in China and Japan have been analyzed. Base on the differences of outward FDI between China and Japan, some shortages of China’s outward FDI have been evaluated. At last, based on the problems of outward FDI in China, some development strategies have be proposed.